On seeing yellow: the case for, and against, short-wavelength light-absorbing intraocular lenses. - Simunovic, M (2012)
The normal human crystalline lens absorbs UV and short-wavelength visible electromagnetic radiation. Early intraocular lenses (IOLs) permitted the transmission of such radiation to the retina following cataract extraction. Experimental studies of the absorption profile of the crystalline lens and animal studies demonstrating the deleterious effects of short-wavelength radiation on the retina led to the development of UV-absorbing, and later, short-wavelength light-absorbing (SLA) IOLs. Short-wavelength light-absorbing IOLs were designed to mimic the absorption properties of the normal crystalline lens by absorbing some short-wavelength light in addition to UV radiation; however, debate continues regarding the relative merits of such lenses over UV-absorbing IOLs. Advocates of SLA IOLs suggest that they may theoretically offer increased photoprotection and decreased glare sensitivity and draw on in vitro, animal, and limited clinical studies that infer possible benefits. Detractors suggest that there is no direct evidence supporting a role for SLA IOLs in preventing retinal dysfunction in humans and suggest that they may have negative effects on color perception, scotopic vision, and circadian rhythms. This article examines the theoretical and empirical evidence for, and against, such lenses.